INFLUENCE OF DIAGNOSTICALLY-DETERMINED CLINICAL DECISIONS ON A TREATMENT IN PATIENTS WITH MANDIBULAR PARTIAL TEETH LOSS - R. Bratus-Hrynkiv (Український стоматологічний альманах, 2018)
According to numerous scientific studies patients with mandibular partial teeth loss need fixed, removable or combined dentures. It is determined by topography of toothless areas, abutment teeth status, presence of occlusal pairs and status of alveolar bone and mucous membrane [1,2,3,4,5].